PHYSICOCHEMICAL AND MINERAL PROPERTIES OF FRUIT PULP AND VEGETABLE OIL OBTAINED IN THE CERRADO BIOME - David Johane Machate (2023)
Cerrado biome is a second major area with 22% of extension, localized in central region of Brazil, which Mato Grosso do Sul state is found with 61% of this biome. Mato Grosso do Sul state is a home of the approximately 4,000 of native Angiosperm species catalogued. Among them stand out pequi, baru, guavira, cajuzinho, etc., because some of them are source of fruits, seeds, nuts, with high bioactive compound and nutritional content. Moreover, species as bocaiuva, guavira, baru provide vegetable oil of high nutritional quality for human consumption. In addition, the soils of the Cerrado region are arable for several crops such as soybean, sunflower, corn, peanut, coffee, cotton sugarcane, and others, which are used for human and animal consumption. Therefore, the Cerrado natural soil is characterized by high amount of aluminium (Al), and with low contents of phosphorus (P), zinc (Zn), iron (Fe), vanadium (V), chromium (Cr), barium (Ba), lead (Pb), nickel (Ni), copper (Cu), molybdenum (Mo) and cadmium (Cd). For this reason, biosolid, manure, fertilizer, and pesticides are massively used for Cerrado soil correction that are rich in minerals, which can contaminate soils, crops and native plants. Although, the consumption of food that are source of minerals (macro– and microelements) is largely recommended for health promotion and disease prevention, however high amount of these minerals can be toxic and hazard for several organs functions. Thus, two chapters are described in this work, which the first chapter present studies conducted with pulp of Campomanesia adamantium (guavira) fruit obtained from the roadside (500 m), bush (1000 m) and farm-margin (3000 m) measured from the road, mineral amount were potassium, lead, phosphorus, arsenic, selenium, iron, molybdenum, zinc, cobalt, nickel, manganese, and chromium were quantified and compared with Dietary Reference Intakes (DRI), the Food Agriculture Organization of the United Nations (FAO) and World Health Organization (WHO) and the Food and Drug Administration (FDA) established limits. The second chapter report studies realized with sunflower oil obtained from dried hull seeds sample cold-press extracted using a domestic machine, which were evaluated the fatty acids composition, physicochemical and optical properties, thermal and oxidative stability were compared with previous studies, however the mineral elements Mg, Cr, Mn, Fe, Co, Ni, Cu, Zn, Cd, Al, Pb, As, and Se were quantified by inductively coupled plasma optical emission spectroscopy (ICP OES) and compared with DRI/AI, and FAO/WHO parameters. Keywords: Cerrado, vegetable, pulp; seed, oil, mineral, non-carcinogenic indices.